Foaming of EVA/starch blends: Characterization of the structure, physical properties, and biodegradability - Rodriguez-Perez, M. A.; Simoes, R. D. [UNESP]; Roman-Lorza, S.; Alvarez-Lainez, M.; Montoya-Mesa, C.; Constantino, C. J.L. [UNESP]; De Saja, J. A. (Wiley, 2012)
Foams produced from blends of an ethylene-vinyl acetate copolymer (EVA) with high VA (vinyl acetate) content (28%) and corn starch have been successfully fabricated using an improved compression molding technique. A detailed characterization of the structure and physical properties has been carried out. The results showed that the corn starch acts as filler for EVA, showing a good compatibility with the polyolefin. Different types of cellular structure (closed, partially interconnected, and fully interconnected) and cell sizes were obtained depending on the relative density and the amount of starch included in the composition. Besides, the addition of starch allows tailoring the physical properties of the composite foams. An increase in the starch content leads to an increase of the density, compressive strength, hardness, and thermal conductivity and a decrease of the elasticity. Finally, biodegradability tests showed how increases the biodegradation with the amount of starch in the foam, which reaches 60% at 100 days for the foam with 70% of starch. © 2011 Society of Plastics Engineers.